Το χειρόγραφο Ραιδεστηνού - Πλεμμένος, Ιωάννης Γ. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1999)
This article deals with a Greek musical collection, so-called the Raidestenos manucript, after its last occupant, George Raidestenos, a Greek cantor and music-teacher in late 19th century Constantinople, and is now held in the Music Folklore Archives, Centre of Asia Minor Studies, Athens. The collection contains 123 Greek secular songs, so-called Phanariot, after the Phanariots, residents of the Phanar district, Constantinople (seat of the Greek Orthodox Patriarchate), who formed the Greek social elite in the 18thcentury Ottoman Empire. These songs were written in neo-Byzantine notation, and employ Turkish modal and rhythmic principles (makam and usui respectively) with Greek text. As it is usual with the Phanariot collections at large, the Raidestenos manuscript is untitled, undated, and anonymous. It consists of two parts, each one written by a different scribe: the first one (pp. 1-26, 20 songs) has been identified by this author with Nikephoros Nautouniares, a Greek archdeacon and music teacher who lived in the early 19th century, and is the compiler of (at least) one more collection of the sort (1818) and other anthologies of Greek church music. The second part (pp. 17-64), while sharing quite a few items with the first, cannot be assigned to a particular author, since its scribe has commited serious (grammatical) mistakes thus leaving the impression that he must have been of origin other than Greek. The importance of the Raidestenos manuscript is twofold: i) it adds decisively to our knowledge about Phanariot musical production of the time, by showing the popularity and stability of this repertoire, since all 123 compbsitions are contained in other contemporary manuscripts with minor alterations (with regard to notation rather than melody), and ii) it enriches the extant number of Phanariot musical collections (10 complete items), most of which are held in Romania, which was governed by the Phanariots as Turkish-appointed officials between 1709 and 1821.